Measurement without management: qualitative evaluation of a voluntary audit & feedback intervention for primary care teams - Daniel J. Wagner; Janet Durbin; Jan Barnsley; Noah M. Ivers (BMC, 2019)
Abstract Background The use of clinical performance feedback to support quality improvement (QI) activities is based on the sound rationale that measurement is necessary to improve quality of care. However, concerns persist about the reliability of this strategy, known as Audit and Feedback (A&F) to support QI. If successfully implemented, A&F should reflect an iterative, self-regulating QI process. Whether and how real-world A&F initiatives result in this type of feedback loop are scarcely reported. This study aimed to identify barriers or facilitators to implementation in a team-based primary care context. Methods Semi-structured interviews were conducted with key informants from team-based primary care practices in Ontario, Canada. At the time of data collection, practices could have received up to three iterations of the voluntary A&F initiative. Interviews explored whether, how, and why practices used the feedback to guide their QI activities. The Consolidated Framework for Implementation Research was used to code transcripts and the resulting frameworks were analyzed inductively to generate key themes. Results Twenty-five individuals representing 18 primary care teams participated in the study. Analysis of how the A&F intervention was used revealed that implementation reflected an incomplete feedback loop. Participation was facilitated by the reliance on an external resource to facilitate the practice audit. The frequency of feedback, concerns with data validity, the design of the feedback report, the resource requirements to participate, and the team relationship were all identified as barriers to implementation of A&F. Conclusions The implementation of a real-world, voluntary A&F initiative did not lead to desired QI activities despite substantial investments in performance measurement. In small primary care teams, it may take long periods of time to develop capacity for QI and future evaluations may reveal shifts in the implementation state of the initiative. Findings from the present study demonstrate that the potential mechanism of action of A&F may be deceptively clear; in practice, moving from measurement to action can be complex.